Lecturer Committee Management System - Mohamed, Hasiah; Nor Adzmi, Nurul Husna Amalina (SOTVI, 2019)
Teaching is the main task of the lecturer besides research,consultancy and holding administrative post. Administrative postconsist of post that need to be held for either two (2) years or 1year depending on the job scope. Currently, there are difficultiesin assign post to lecturer. Beside, it is time consuming to trace thecurrent post of lecturer. In order to solve the current process, asystem known as Lecturer Committee Management System(LCMS) is proposed. LCMS can be used to propose and assignpost to lecturer and to track lecturer involvement history incommittee. The method use in the development of LCMS isRapid Application Development (RAD) model. Once thedevelopment process completed, expert evaluation and userevaluation have been conducted. For the expert there are a fewquestion that have been asked in order to improve the usabilityand functionality of the LCMS. For the user, there are sixconstruct provided in order to evaluate LCMS. The result showthat respondents agree LCMS is easy to use with the highestmean is 4 (SD=0.41). Lastly, as for the future enhancement newfeatures such as lecturer can get the notification about postassigned via phone.